A simple approach to the elasto-plastic coupling analyses of circular tunnels in confining pressure-dependent strain-softening rock masses. Issue 5 (3rd September 2017) - Zhang, Qiang; Li, Cheng; Guo, Qiang; Min, Ming; Wang, Yanning; Jiang, Binsong
Abstract: The conventional strain-softening behaviors which assume the strength parameters as the functions of the plastic strain have been studied using various methods. However, rock-like materials have also been found to manifest pressure-dependent behavior for both elastic and plastic rock masses. The realization of the radial stress was found to be continuous, and gradually increased from supporting stress to in situ stress for the circular openings under hydrostatic pressure. The radial stress was spaced as numbers of sections, and each annulus was considered as an ideal plastic rock mass. The close-formed analytical solutions of each annulus can be easily obtained. Therefore, using the displacement continuum and stress boundary conditions, the dimensionless radius corresponding to the spaced radius could be derived. The radial stress and plastic shear strain at the inner radius of the outer adjacent annulus were employed to describe the material property evolution law. Then, the radii could be recursively obtained. Finally, for the conventional strain-softening rock masses, the pressure-dependent elastic rock and elasto-plastic coupling strain-softening rock masses were employed to validate the proposed approach. In this study, having completed the above steps, it was concluded that the results were in accordance with the numerical methods.